Virtual Exchange as a Third Space to Decolonise ELT (VETSDELT) project: report on its first action-research cycle - Joanne Marsh, Michelle Mayer (Discussing Global Citizenship through Collaborative Online International Learning (COIL) - Virtual Exchange (VE) in Language Learning and Teaching: Symposium Proceedings, 2023)
This paper aims to report on the VETSDELT (Virtual Exchange as a Third Space to Decolonise English Language Teaching) project. Its focus was to stimulate a reflection on English, ELT, and the ‘native-speakerism’ ideology through a Virtual Exchange (VE) as a safe Third Space. The paper illustrates how students and tutors engaged in English language teacher education in universities in Brazil, Spain, the UK, and Sri Lanka reflected on ELT in a series of synchronous dialogic sessions on Zoom. The paper reports on the initial findings stemming from cycle one of VETSDELT, which ran between November and December 2022 and involved 44 participants. The initial data analysis showed that VE could facilitate intercultural and international knowledge exchange in a safe Third (online) Space.